A Cross-Sectional Comparative Correlation Study of Computed Tomography and Magnetic Resonance Imaging in the Evaluation of Pediatric Hydrocephalus . - Dr. Kamal Nayan Gangey; Dr Prashant Kumar Sinha (Student's Journal of Health Research Africa, 2026)
Background: Hydrocephalus is a common pediatric neurosurgical disorder characterized by abnormal cerebrospinal fluid (CSF) accumulation, leading to ventricular dilatation and raised intracranial pressure. CT is the preferred emergency imaging modality because of its rapid acquisition, whereas MRI provides superior soft tissue characterization without ionizing radiation. This study compared the diagnostic performance and correlation of CT and MRI in pediatric hydrocephalus. Aim: To compare the diagnostic performance of CT and MRI and determine the correlation between their imaging findings in pediatric hydrocephalus. Materials and Methods: A hospital-based prospective observational comparative study was conducted over 18 months in 80 children (0–18 years) with suspected hydrocephalus who underwent both CT and MRI. Imaging findings were compared using sensitivity, specificity, diagnostic accuracy, Cohen's kappa, and Pearson's correlation coefficient. Results: The mean age was 4.9 ± 3.8 years, and 58.8% were males. Both CT and MRI detected ventricular dilatation in 100% of cases. MRI identified significantly more aqueductal stenosis (27.5% vs. 20.0%, p=0.028), congenital anomalies (31.2% vs. 22.5%, p=0.019), posterior fossa lesions (15.0% vs. 10.0%, p=0.041), and periventricular edema (70.0% vs. 48.8%, p=0.006) than CT. CT demonstrated 91.3% sensitivity, 95.0% specificity, and 92.5% diagnostic accuracy. Agreement between CT and MRI was excellent (κ=0.88), with a strong correlation for ventricular size assessment (r=0.93, p<0.001). Conclusion: CT is an effective first-line imaging modality for rapid diagnosis, whereas MRI is superior for etiological evaluation, treatment planning, and follow-up in pediatric hydrocephalus. Recommendation: CT should be used for initial evaluation, particularly in emergencies, while MRI should be preferred for comprehensive assessment. Larger multicenter studies are recommended to validate these findings.